The effect of corporate social responsibility on financial performance with real manipulation as a moderating variable - Rahmawati; Setyaningtyas Honggowati; Edy Supriyono (International Journal of Management, Economics and Social Sciences (IJMESS), 2014)
This study aimed to obtain empirical evidence about the effect of real manipulation practices on Corporate Social Responsibility (CSR), and further examined the impact of real manipulation on relationship between CSR and the financial performance of companies in the future. 27 companies listed on Indonesian Stock Exchange during the years 2006 - 2008 were selected as sample for this study. Data were collected by purposive sampling method and statistical method used for analysis was ordinary least square regression. The study provided empirical evidence that companies engaged in the practice of real manipulation had no influence on CSR activities. The results showed that the higher level of real manipulation on operation cash flow leads to negative effect on the relationship between CSR and financial performance.
Keywords: M14; G39; O16; 330; Corporate Social Responsibility (CSR); real manipulation; corporate financial performance; manufacturing company; Indonesia